2019
DOI: 10.1016/j.neuron.2019.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Protease Cleavage of Host Protein Septin-2 Mediates Mitotic Defects in Neural Progenitors

Abstract: SUMMARY Zika virus (ZIKV) targets neural progenitor cells in the brain, attenuates cell proliferation, and leads to cell death. Here, we describe a role for the ZIKV protease NS2B-NS3 heterodimer in mediating neurotoxicity through cleavage of a host protein required for neurogenesis. Similar to ZIKV infection, NS2B-NS3 expression led to cytokinesis defects and cell death in a protease activity-dependent fashion. Among binding partners, NS2B-NS3 cleaved Septin-2, a cytoskeletal factor involved in cytokinesis. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 66 publications
(76 reference statements)
1
58
0
3
Order By: Relevance
“…Beyond a genetic basis, microcephaly is also caused by viral infection, notably Cytomegalovirus or Zika virus (ZIKV) infection during pregnancy [25]. Several studies have shown that acute ZIKV infection can also impair neural progenitor mitosis and in some cases is associated with aberrant neurogenesis and apoptosis in human and mouse models [26][27][28][29]. Thus, both genetic and viral causes of microcephaly are linked to progenitor mitosis defects and similar alterations in neurogenesis and cell survival.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond a genetic basis, microcephaly is also caused by viral infection, notably Cytomegalovirus or Zika virus (ZIKV) infection during pregnancy [25]. Several studies have shown that acute ZIKV infection can also impair neural progenitor mitosis and in some cases is associated with aberrant neurogenesis and apoptosis in human and mouse models [26][27][28][29]. Thus, both genetic and viral causes of microcephaly are linked to progenitor mitosis defects and similar alterations in neurogenesis and cell survival.…”
Section: Introductionmentioning
confidence: 99%
“…Previous data showed that NS4AB interferes with the mTOR pathway in NPCs, reducing proliferation and inducing autophagy 45 , and that NS2A interacts with AJs, while disrupting the integrity of the developing neuroepithelium and again, perturbing NPC proliferation 20 . Recently, the NS2B3 heterodimer was also shown to disturb the cell-cycle as it affects the host protein Septin-2 that is involved in NPCs cytokinesis 46 . To date, NS5 has only been shown to counteract host antiviral mechanisms by targeting the interferon pathway 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Considering the role of septins in membrane curvature recognition, it would be interesting to address whether recruitment of septins to sites where CEV fuses with the plasma membrane depends on membrane curvature. Interestingly, new work has shown that the protease NS2B-NS3 heterodimer from Zika virus, a mosquito-transmitted Flavivirus that causes microcephaly, can mediate cytokinesis defects and cell death through cleavage of SEPT2 (Li et al, 2019). The role of septins in infection by other pathogenic viruses has not yet been tested.…”
Section: Septin Entrapment Of Vaccinia Virusmentioning
confidence: 99%